2020
DOI: 10.1089/gyn.2019.0074
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection as Part of Cytoreductive Surgery for Ovarian Cancer

Abstract: Objective: The aim of this study was to describe and evaluate the safety of hepatic resections for ovarian cancer liver metastases and the benefit in terms of survival as part of cytoreductive surgery among peritoneal seeding and parenchymal metastases. Materials and Methods: Data were reviewed retrospectively from patients who underwent liver resection as part of cytoreductive surgery for ovarian cancer at the Instituto Nacional de Enfermedades Neoplásicas, in Lima, Perú, patients underwent surgical cytoreduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, studies have shown that performing cytoreductive surgery, including hysterectomy, bilateral salpingo-oophorectomy, omentum resection, and resection of all metastatic lesions, is beneficial to the survival of patients ( 13 ). Performing complete resection of liver metastases can confer benefits to survival ( 14 ). A patient’s disease-free survival and overall survival improve ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that performing cytoreductive surgery, including hysterectomy, bilateral salpingo-oophorectomy, omentum resection, and resection of all metastatic lesions, is beneficial to the survival of patients ( 13 ). Performing complete resection of liver metastases can confer benefits to survival ( 14 ). A patient’s disease-free survival and overall survival improve ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 28 studies were subsequently excluded after the examination of full text (if available); in details, one because only the abstract was retrieved, three for language different from English and 24 because they didn't meet the population and intervention inclusion criteria of this study. Finally, 10 articles were included in our systematic review [17,[19][20][21][22][23][24][25][26][27] (Fig. 1).…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
“…All data about general characteristics and liver metastases characteristics and their surgical treatment are reported in Tables 1 (Ref. [13,[15][16][17][18][19][20][21][22][23]) and 2 (Ref. [13,[15][16][17][18][19][20][21][22][23]), respectively.…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations